Spent mushroom substrate for eucalyptus seedling growth under varying water deficiency conditions - Postinguel, Rafael de Barros [UNESP]; Alves, Lucas da Silva [UNESP]; Ré, Beatriz Bruno [UNESP]; Caitano, Cinthia Elen Cardoso [UNESP]; Barretto, Vitor Corrêa de Mattos [UNESP]; Zied, Diego Cunha [UNESP] (Springer Nature, 2025)
Eucalyptus, a globally prevalent species, holds significant prominence in Brazil, expanding even into regions with water deficits and low soil fertility. Addressing this requires effective techniques and strategies for cultivating seedlings to ensure optimal post-transplant development. This study delved into the potential of spent mushroom substrate (SMS) as a substitute for conventional peat-based substrates, particularly in the context of water deficit conditions post-transplantation. The experiment unfolded in two distinct stages. Firstly, seedling production in nursery entailed an assessment of varying proportions of SMS in the peat-substrate, with or without mineral fertilizer. This initial phase revealed significant increases in key variables, such as height, collar diameter, and shoot fresh matter, as SMS proportions increased. Notably, a complete replacement of peat could be achieved by utilizing 100% SMS. Mineral fertilization emerged as a crucial factor, significantly enhancing the quality and robustness of seedling for subsequent transplanting. It increased the Dickson Quality Index by more than 30% compared unfertilized treatment. The second stage involved transplanting SMS-incorporated seedlings into different water conditions: no drought, moderate drought, and severe drought. Observations indicated that seedlings enriched with SMS and mineral fertilization exhibited an increase in root dry matter with 25–50% peat substitution under moderate water restrictions. This underscores SMS’s potential as a sustainable alternative to peat and a strategic tool for alleviating water stress in specific eucalyptus production scenarios. In conclusion, the study confirms the intrinsic value of SMS in promoting eucalyptus seedling growth when combined with mineral fertilization of the substrate. Besides its environmental benefits, SMS shows promise in optimizing water management practices, offering a sustainable solution for eucalyptus cultivation.
Keywords: Mushroom compost; Nursery seedlings; Organic amendment; Root dry matter; Water available